2021
DOI: 10.1021/acs.jmedchem.0c02000
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Y4 Receptor Antagonist Binds in an Allosteric Binding Pocket

Abstract: Human neuropeptide Y receptors (Y 1 R, Y 2 R, Y 4 R, and Y 5 R) belong to the superfamily of G protein-coupled receptors and play an important role in the regulation of food intake and energy metabolism. We identified and characterized the first selective Y 4 R allosteric antagonist (S)-VU0637120, an important step toward validating Y receptors as therapeutic targets for metabolic diseases. To obtain insight into the antagonistic mechanism of (S)-VU0637120, we conducted a variety of in vitro, ex vivo, and in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 54 publications
1
33
0
Order By: Relevance
“…With respect to the N‐terminus of the ligand, our model does not predict direct interactions with the Y 5 R, similar to the NPY‐Y 2 R and PP‐Y 4 R models, [11–13] whereas the N‐terminus of NPY was suggested to interact extensively with Y 1 R [9] . Indeed, N‐terminally truncated NPY can bind Y 2 R but not Y 1 R [40] .…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations
“…With respect to the N‐terminus of the ligand, our model does not predict direct interactions with the Y 5 R, similar to the NPY‐Y 2 R and PP‐Y 4 R models, [11–13] whereas the N‐terminus of NPY was suggested to interact extensively with Y 1 R [9] . Indeed, N‐terminally truncated NPY can bind Y 2 R but not Y 1 R [40] .…”
Section: Discussionmentioning
confidence: 46%
“…[11] Q 3.32 is highly conserved among the YRs and this interaction likely represents ah allmark for the entire multiligand/multireceptor system. [21] With respect to the N-terminus of the ligand, our model does not predict direct interactions with the Y 5 R, similar to the NPY-Y 2 Ra nd PP-Y 4 Rm odels, [11][12][13] whereas the Nterminus of NPY was suggested to interact extensively with Y 1 R. [9] Indeed, N-terminally truncated NPY can bind Y 2 Rbut not Y 1 R. [40] Interestingly,w hile Ala substitution the Nterminus of NPY barely affected Y 5 Ra ctivation, truncation of the 12 N-terminal residues reduced the potencyo ft he ligand by 8-fold. As altering the structure of the N-terminal region of NPY can heavily affect ligand potencye ven at YR subtypes that tolerate its truncation, [41] the N-terminal segment may stabilize the overall conformation of the peptide.…”
Section: Methodsmentioning
confidence: 69%
See 2 more Smart Citations
“…Solution NMR studies showed a different structure with the helix present through the C-terminal end of the peptide [ 140 ]. The recent mutagenesis and docking study also suggested that the C-terminus of PP needed to unwind to bind to the Y 4 receptor [ 141 ]. Characterization of NPY in the membrane-bound state by NMR, CD, and EPR found the helix extending from residue 14 through the C-terminus [ 142 , 143 ].…”
Section: Structural Changes In Peptides Induced By Receptors Are Critical For Bindingmentioning
confidence: 99%